Accelerated Repayment of Murabahah Agreement in Sharia Banking - Susandi, Adi; Al Hakim, Sofian (Islamicate Institute, 2020)
Banking growth in Indonesia has started to improve, as seen in the financing conducted by sharia banks as well as credit in conventional banks. In the midst of the current crisis, Sharia banking continues to face a very rapid development in the muslim-majority community. Sharia banking is the performance of the Sharia industry in Indonesia where its role has been recognized legally and able to compete with conventional banking. The impact of it all will bring about competition that allows for accelerated repayment especially in terms oftakeovers. This study aims to analyze how financing practices, especially murabahah agreements in sharia banks and if there is a settlement in the accelerated then reviewed with the study of fiqhnya and in ju paired with what happens in conventional banks. This qualitaf research by means of ( Descriptive Analytics) where information is collected using a very in-depth interview method and literature, after that in the analysis until finding conclusions. This study provides the result that murabahah contract financing and repayment in accelerated both in sharia and conventional banking has been in accordance with the requirements and regulations in force, but still needed will be government intervention in the manufacture of regulations to create a more ethical competitive climate, especially that can result in accelerated repayment so that often takeover financing or credit from sharia banks to conventional and vice versa. The implications of this study to share knowledge to the public who still lack understanding between financing, especially murabahah agreement and repayment in accelerated that occurs in Sharia banking. So it is expected to provide in-depth guidance as knowledge to make decisions between sharia or conventional banks in an effort to meet the needs of financing.